NUCLEAR-FUELED CIRCULATORY SUPPORT SYSTEMS IV: RADIOLOGIC PERSPECTIVES - Huffman, F. N. (1974)
If an implantable artificial heart can be developed, it should prove beneficial to a significant group of patients. A variety of energy sources, such as biologic, electromagnetic, and nuclear, are under evaluation. Currently, biologic fuel cell technology is not sufficiently advanced to permit its extrapolation to the power levels required for implantable circulatory support systems. Electromagnetic systems have the disadvantage of heavy batteries of considerable bulk requiring frequent recharging. Radioisotope-fueled thermal engine systems have the potential of providing degrees of freedom not possible with rechargeable units. However, radiosotope circulatory support systems subject their recipients to prolonged intracorporeal radiation, add to environmental background radiation, and constitute an exceedingly small, but finite, hazard due to possible violation of fuel containment.